2017
DOI: 10.3892/ol.2017.6075
|View full text |Cite
|
Sign up to set email alerts
|

SPARC overexpression suppresses radiation-induced HSP27 and induces the collapse of mitochondrial Δψ in neuroblastoma cells

Abstract: Neuroblastoma is the cause of >15% of cancer-associated mortality in children in the USA. Despite aggressive treatment regimens, the long-term survival rate for these children remains at <40%. The current study demonstrates that secreted protein acidic and rich in cysteine (SPARC) suppresses radiation-induced expression of heat shock protein 27 (HSP27) in vivo and suppresses mitochondrial membrane potential (Δψ) in neuroblastoma cells. In the present study, the overexpression of SPARC in SK-N-BE(2) and NB1691 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…When the concentration of ROS and oxidative stress reaches a certain level, the Δψm would be changed, resulting in the release of apoptosis factors. 30 Here, the results showed that GCP-1 treatments induced the Δψm decline and indicated that the Δψm also played significant roles in the induction of apoptosis.…”
Section: Gcp-1 Induces Hela Cells Apoptosis Through Mitochondrial Pathwaysmentioning
confidence: 67%
“…When the concentration of ROS and oxidative stress reaches a certain level, the Δψm would be changed, resulting in the release of apoptosis factors. 30 Here, the results showed that GCP-1 treatments induced the Δψm decline and indicated that the Δψm also played significant roles in the induction of apoptosis.…”
Section: Gcp-1 Induces Hela Cells Apoptosis Through Mitochondrial Pathwaysmentioning
confidence: 67%
“…Several studies demonstrated that SPARC, GCSF, and IP‐10 were induced higher migration ability in trophoblast cells including various cell line. The SPARC regulates radiation induced HSP expression by inhibiting mitochondrial function, including mitochondrial mass and membrane potential in neuroblastoma cells, and by modulating the extracellular matrix (Furmento et al, 2016; Jiang et al, 2013; Tanpure et al, 2017; Zipin‐Roitman et al, 2007). The MCP‐1/‐3 is related to macrophage migration and infiltration through effects on mitochondrial lipid homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture . Five human PCa cell lines DU145, LNCaP, PC-3, NPC-3 and BPC-3, as well as the control prostate epithelial cell line (RWPE-1 (19,20). The relative mRNA expression levels were normalized to the expression level of GAPDH using the 2 -∆∆Ct method.…”
Section: Methodsmentioning
confidence: 99%